The relationship between social anxiety, procrastination, self-esteem and internet addiction among university students in Malaysia. - Choo, Yun En (2022)

(untitled)
Internet gaming addiction refers to overuse which neglect basic needs depression when the internet is not available, poor performance and social withdrawal. Internet gaming disorder also causes loss of control over the amount of time spent playing games which leads to sacrifices of other hobbies and activities. These study aims to investigate the relationship between social anxiety, procrastination, self-esteem and internet gaming disorder (IGD) among university students in Malaysia. A convenience sampling method was conducted among 111 participants and they were recruited by applying the convenience sampling method. The participants were Malaysian university students which female (n = 72, 64.9%) are more than male (n = 39, 64.93%). The instruments used were Internet Gaming Disorder Scale, Social Interaction Anxiety Scale, Procrastination Scale and Rosenberg Self-esteem Scale. Results shows that social anxiety and procrastination shows positive relationship with Internet Gaming Disorder while self-esteem was negatively correlated with internet gaming disorder. There is no significant difference between male and female in internet gaming disorder. The results of this study will give university counsellors real advice on how to help Malaysian university students who are at a high risk of dropping out by boosting their academic toughness. The results of this study will give university counsellors concrete information on how to assist university students who study at Malaysia who are at a greater risk of having internet gaming addiction.